Predicting groundwater recharge in Ghana by estimating evapotranspiration - Anayah, F. M.; Kaluarachchi, J. J.; Pavelic, Paul; Smakhtin, V. (2023)
This study uses a modified Granger and Gray model to estimate evapotranspiration and then groundwater recharge in Ghana. The overall results show that the model is capable of reliably predicting regional evapotranspiration using a small number of monitoring stations with meteorological data only. This information allows the estimation of groundwater recharge via the water balance equation. The results indicate that the aquifer system is sufficiently recharged, especially in northern Ghana, where dry conditions prevail, to allow the development of groundwater resources to satisfy increasing water demands.